New ichnological material from the Vera Formation (Los Menucos Complex, Triassic), Puesto Vera locality, Río Negro Province, Argentina: a first account - Citton, Paolo (2018)
Fil: Citton, Paolo. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina